IMPLEMENTASI PENDIDIKAN KARAKTER EMPATI DALAM PEMBELAJARAN PAI DI SMPN 5 SINJAI - Nurqadriani; Suriyati; Jamaluddin; Nur, Makmur Jaya; Wafda (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Humans are inseparable creatures. Empathy is the ability to feel and understand the feelings, thoughts and experiences of other people. It involves the ability to put oneself in another person's shoes and see the world from their perspective. The aim of this research is to find out how the implementation of character education strengthens character education in schools, the factors that support and hinder character education in schools, the role of teachers in character education in schools, and the implementation of empathetic character education outside the classroom. Data collection techniques are interviews and observation. The analysis is qualitative descriptive. The results of the study show that learning Islamic Religious Education at school can improve student behavior in the educational environment. The ability to empathize is built through learning experiences, education and socialization. Educators can plan teaching and learning activities that encourage empathetic behavior in students. Role playing, discussions, helping each other, group work and questions and answers are examples of learning activities that are considered important for fostering empathetic behavior Keywords:  Character; Empathy; Pie Learning.